Diversidade beta taxonômica e funcional dos peixes de água doce do Brasil - Santos, Isaac Trindade (2017)
The first part of this work we assess the relationship between the taxonomic and functional alfa- and beta-diversity (TβD and FβD) in primary ray-finned fishes (Actinopterygii) from Brazil, at three different spatial scales. We assess the contribution of the components of β-div – turnover (replacement of species) and nestedness (species loss) – to the observed pattern, and whether they are driven by stochastic or deterministic processes. While TβD was ruled by high rates of turnover (from 93 to 98%), FβD had a greater contribution of nestedness (70 to 80%). Observed TβD was higher than by chance. In addition, environmental filtering and biotic interactions play a greater role for the formation and maintenance of primary ray-finned fish diversity patterns in the Neotropics. In the second part of this work we assessed how the patterns of beta diversity are affected by human actions. Taking the ‘Bento Rodrigues dam disaster’ at the Doce Basin as a case model, we evaluate the possible consequences of different levels of local species extinctions to the regional taxonomic β-div and functional richness across six neighbour river basins. A higher contribution of nestedness (13-19%), leaded to an increase in the pattern of beta diversity: 0.75 to 0.81 (Sørensen dissimilarity index). The functional richness from Doce Basin also decreased from 69-36%. Owing to the regional pattern of species sharing among basins, the likely consequences of fish extinctions include a decreasing trend of turnover contribution (87-81%). The disaster caused substantial changes on regional patterns of β-div and functional richness, owing to a process known as subtractive heterogenization. These findings might be relevant for both, local conservation purposes and the overview of how disturbance affect biodiversity.